Pengaruh Perubahan Tata Guna Lahan Terhadap Kondisi Tata Air Daerah Aliran Sungai (DAS) Tallo: The Impact of Land Use Change on Water Management Conditions of Tallo Watershed - Fatiawan, Engki; Zubair, Hazairin; Lias, Syamsul Arifin (Jurnal Ecosolum, 2024)
Land use conversion affects the water management of a watershed, leading to flooding, erosion, and sedimentation. Tallo Watershed located in South Sulawesi is considered critical due to frequent flooding. This study aims to change the land use of the Tallo River Watershed (DAS) and its influence on watershed performance in terms of water management aspects. The methods used include spatial analysis with supervised classification to examine land cover changes and the Ministry of Forestry Regulation No. P61 of 2014 for water management evaluation. The largest land use conversion occurred in paddy fields, which decreased by 3,731.37 hectares, shrubs decreased by 1,484.87 hectares, mixed dryland agriculture by 1,017.29 hectares, water bodies by 317.60 hectares, mangrove forests by 218.27 hectares, and swamp shrubs by 26.99 hectares. These areas were converted into settlements covering 4,348.42 hectares, dryland agriculture 2,070.95 hectares, plantation forests 155.63 hectares, secondary dryland forests 34.01 hectares, airports 93.80 hectares, fish ponds 68.16 hectares, open land 19.16 hectares, and savannas 6.25 hectares. From the water management aspect, Flow Regime Coefficient value was >110, classified as very high, Annual Flow Coefficient was >0.5, also very high; sediment load and flooding were categorized as very high, and Water Usage Index value was <1700, categorized as very poor. As a result, the water management of the Tallo Watershed is classified as very poor, with a score of >130. The water management carrying capacity of Tallo Watershed falls into very poor classification from 2003 to 2022, mainly due to land use conversion and forest area covering only 11% of the total Tallo Watershed area.